EP1195 Circulating microRNAs in differential diagnosis of vulvar intraepithelial lesions and vulvar squamous cell carcinoma. (1st November 2019) - Zalewski, K; Szczyrek, M; Kowalik, A; Długosz, A; Misiek, M; Bidziński, M; Goryca, K; Kowalewska, M
Abstract : Introduction/Background: Vulvar squamous cell carcinoma (VSCC) develops from vulvar squamous intraepithelial lesions (VIN). VIN is subdivided into two types, high grade-squamous intraepithelial lesion (HSIL) and differentiated vulvar intraepithelial neoplasia (dVIN), which differ by pathogenesis and clinical course. No molecular markers allowing precise and non-invasive diagnosis and/or differentiation of malignant and premalignant lesions of the vulva have been developed to date. This study aimed to identify circulating microRNAs as markers for differential diagnostics of VIN and VSCC. Methodology: Expression levels of 20 microRNAs were analyzed by quantitative RT-PCR in the plasma samples of 19 patients with VIN (HSIL and dVIN), 41 patients with VSCC and 15 healthy female donors (control group). The microRNA levels were normalized to hsa-miR-93-5p and hsa-miR-425-5p. Results: The levels of three microRNA molecules, namely miR-7-5p, miR-630 and miR-23b-3p were found to differentiate plasma samples of obtained from healthy donors, VIN and VSCC patients. The levels of miR-7-5p and miR-630 were decreased in blood of patients with VSCC as compared to VIN and controls. In contrary, the levels of miR-23b-3p were decreased in the blood of VSCC patients as compared to VIN and healthy donor samples. These differences were statistically significant. Conclusion: Our data reveal high diagnostic potential of the assessment of levels of circulating miR-7-5p, miR-23b-3p and miR-630 in VIN and VSCC patients. Disclosure: Nothing to disclose